Komunikasi KPU Kota Denpasar Dalam Sosialisasi PILWALI 2020 Di Tengah Pandemi Covid-19 - Cahyaning Dewi, Ni Luh Manik; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2021)
This research is entitled "Denpasar City KPU Communications In Disseminating the 2020 PILWALI Amid the Covid-19 Pandemic". The purpose of this study was to find out how political communication was carried out by the Denpasar City KPU in disseminating the election in the midst of the Covid-19 pandemic. This study uses a qualitative descriptive method with Harold Lasswell's Political Communication Theory and Schoreder's Political Communication Strategy Theory (Offensive Strategy for market expansion and market penetration). Informants in this study amounted to 2 people who were determined by purposive sampling. Data were collected through interviews, observation and documentation. The results showed that the Denpasar City KPU in 2020 only experienced a 2% decrease in public participation from the 2015 election which reached a 5% decline.     Keywords: Political Communication, Denpasar City Election Commission, PILWALI Socialization in a Pandemic